(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
The article describes the lexical features of toponyms in Alisher Navoi’s epic "Layli and Majnun". The onomastic scope of the epic, i.e., the issues of using proper nouns, was analyzed.